PENGARUH NON PERFORMING FINANCING (NPF), FINANCING TO DEPOSIT RATIO (FDR) DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP PROFITABILITAS (ROA) PADA BANK UMUM SYARIAH DI INDONESIA - Randi Pratama; Akhmad Nur Zaroni; Kokom Komariah (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This research is motivated by the growth of Islamic banking, especially Islamic commercial banks in Indonesia, which are currently increasingly widespread and in demand by the Indonesian people, seen from the growth of banking and other sharia-based financial institutions from year to year. And the development of Islamic banks in Indonesia is a benchmark for the success of the existence of Islamic Economics.. This study aims to determine and analyze the effect of NPF, FDR, and CAR partially and simultaneously on ROA at Islamic Commercial Banks in Indonesia for the period 2017-2021. The research method used is quantitative research. The population in this study is BUS registered with OJK during the 2017-2021 period. The sample used is 9 Islamic Commercial Banks. This study uses a sampling technique with purposive sampling. The data is obtained from the financial statements of each BUS which is located on the official website of each Bank. Based on the tests that have been carried out in this study, the results show that NPF and CAR have a partial effect on ROA at Islamic Commercial Banks in Indonesia marked by a significant value of 0.000 <0.05. Meanwhile, FDR does not have a partial effect on ROA at Islamic Commercial Banks in Indonesia, marked by a significant value of 0.398 > 0.05. Simultaneously NPF, FDR and CAR have an effect on ROA at Islamic Commercial Banks in Indonesia marked by a significant value of 0.000 <0.05.